Study of the inhibitory effects of Andrographis paniculata on bacteria causing skin infection / Rashidah Iberahim and Nor Akmalazura Jani - Iberahim, Rashidah; Jani, Nor Akmalazura (2011)
Andrographis paniculata (AP) or hempedu bumi belonging to family Acanthaceae is traditionally used in China and India to cure skin infection. This herb was also believed to treat common cold, diarrhea, liver diseases, inflammation and also suggested as a new way to treat HIV infection and other related immune disorder. The antimicrobial effects were studied on three parts of the plant which were leaf, stem and root. These parts were extracted using hexane, ethyl acetate and methanol. All extract were screened using discs diffusion method against seven bacteria causing skin disorder. The tested bacteria were: (4 Gram-positive: Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis and Streptococcus pneumonia) and (3 Gram-negative strains: Proteus vulgaris, Pseudomonas aeroginosa, Klebsiella pneumoniae). The penicillin G and Streptomycin Sulfate were used as the positive control, while methanol was used as negative control. The active extracts possessed relative antibacterial activity against the tested microorganisms with the diameter of inhibition zones between ± 7 to 13 mm. The methanol extract of the leaf inhibited S. epidermidis growth with inhibition zone diameter around 10 mm, while the methanol extract of the root showed the inhibition toward K. pneumoniae with the same size of inhibition zone diameter. The extraction of stem using hexane showed sensitivity towards B. subtilis with ± 11 mm. On the other hand, the ethyl acetate extract of the root was susceptible against S. pneumoniae (± 9 mm). The stem methanol extract of AP showed the highest inhibitory effects against S. aureus with ±13mm diameter compared to other bacteria tested. The ethyl acetate extract of the stem and the hexane extract of the leaf showed a significant activity against four bacteria (± 8 - 11 mm diameter) which were S. pneumonia, K. pneumonia, P. aeroginosa and S. epidermidis. These results may suggest that the stem of A. paniculata possess compounds with antibacterial property which can be used as antibiotic therapy for skin infection treatment.